Long‐term functional and esthetic outcomes after fibula free flap reconstruction of the mandible. Issue 7 (13th February 2019) - Petrovic, Ivana; Baser, Raymond; Blackwell, Timothy; McCarthy, Colleen; Ganly, Ian; Patel, Snehal; Cordeiro, Peter; Shah, Jatin
Abstract: Background: The goal of this study is to report functional and esthetic outcomes, after fibula free flap (FFF) reconstruction of the mandible for oral cancer, assessed by physicians, nonclinicians, and patients. Methods: Twenty‐five long‐term survivors from oral cancer after FFF reconstruction were recalled for head and neck examination by surgeons, for photographs and patient‐reported outcomes, using EORTC, QLQ‐C30, H&N35, and FACE‐Q questionnaires. Results: Physicians reported 64% restoration of functionality compared to normal. Patients reported high scores on QLQ‐C30 but lower scores on H&N35. Esthetic scores were reported higher by clinicians than nonclinicians. The decline in function and appearance was attributed to loss of lower dentition, trismus, malocclusion, xerostomia, and tissue atrophy. Conclusion: To minimize the decline in function and appearance, immediate dental implants in FFF, better reconstruction of the temporomandibular joint, newer methods of radiotherapy to minimize xerostomia and oral exercises to prevent trismus should be considered.